IMPLEMENTATION OF BLENDED LEARNING STATION ROTATION TYPE FOR STRENGTHENING CHARACTER EDUCATION IN CLASS V STUDENTS LEARNING PKN AT SDIT DAROJAATUL ULUUM - sri - imawati (FALASIFA : Jurnal Studi Keislaman, 2023)
The industrial revolution 4.0 is an era of life that leads to technology. Mastery in the field of technology is a challenge for humans at this time, mastery of technology is expected to make it easier for humans to overcome problems that exist in the era of revolution referred to in the field of Education. This research was conducted based on the problems found in class 5C at SDIT Darojaatul Uluum. This study aims to determine the strengthening of communicative, creative and responsible character education. The method used in this research is case qualitative research. Data collection techniques with observation, interviews and documentation. The results of the study found that the station rotation type Blended learning can be effective in strengthening communicative, creative and responsible character education. This is experienced by students based on being able to follow a series of learning by trying to find out more deeply to find out new things, being able to open up relationships and communicate with group mates. In addition, students can carry out their duties and obligations as well as possible in accordance with the instructions given by the teacher.